2014
DOI: 10.1007/s11427-014-4699-x
|View full text |Cite
|
Sign up to set email alerts
|

T lymphocytes and aortic aneurysms

Abstract: Aortic aneurysms are common and life threatening problems with high rates of death. The initiation and progression of aneurysms are characterized by extensive extracellular matrix degradation and immune cells invasion within arterial wall. During the pathogenesis of all aneurysms, inflammation and immune cells play a significant role. Although T cells are abundant in aneurysm tissue, their functions in initiation and propagation of aneurysms remain unclear. This review summarizes the current state of knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 70 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…The role of T-cells in aneurysms is largely unclear ( 23 ). A recent study of human abdominal aortic aneurysms unveiled an association of tissue-infiltrating T-cells with disease severity ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of T-cells in aneurysms is largely unclear ( 23 ). A recent study of human abdominal aortic aneurysms unveiled an association of tissue-infiltrating T-cells with disease severity ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…32 Lymphocytes play a role in AAA pathogenesis through secretion of cytokines, modulation of inflammatory process, and extracellular matrix remodeling. 33,34 The modulation of their count and activation might thus be involved in pathophysiological features leading to AAA formation and impact on the postoperative outcome in patients undergoing surgical repair. All in all, PLR represents a marker of systemic inflammation and extreme values are predictive of postoperative events in patients undergoing AAA surgical repair.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that the aortic walls of TAA patients display significantly more T cells than those in normal aortas. However, it should be noted that different T cell subsets have complex effects during the inflammatory response and might even contradict each other ( 44 ). For example, Th1 and Th2 (subsets of naïve CD4-positive T cells) are characterized by the production of IFN-γ and IL-4, respectively ( 45 ).…”
Section: Discussionmentioning
confidence: 99%